Topological Structural Stability of Partial Differential Equations on Projected Spaces - Aragão-Costa, E. R.; Figueroa-López, R. N. [UNESP]; Langa, J. A.; Lozada-Cruz, G. [UNESP] (Springer Nature, 2018)
In this paper we study topological structural stability for a family of nonlinear semigroups Th(·) on Banach space Xh depending on the parameter h. Our results shows the robustness of the internal dynamics and characterization of global attractors for projected Banach spaces, generalizing previous results for small perturbations of partial differential equations. We apply the results to an abstract semilinear equation with Dumbbell type domains and to an abstract evolution problem discretized by the finite element method.
Keywords: Attractors; Dumbbell domains; Gradient semigroups; Structural stability